AWARENESS OF MATERIALITY IN TIME AND CONDITION. THOUGHTS ON THE RELATION BETWEEN ART HISTORY AND CONSERVATION - Andreas Huth; Katharine Stahlbuhk (Ochrona Dziedzictwa Kulturowego, 2019)
Art historical research needs to consider the materiality of artefacts, but the character of the material and the state of preservation of any object change over time. Today’s restoration and conservation sciences provide the basis for present research in the field of history of art and architecture. Following this premises and with some examples from current research projects our contribution tries to show how much the contemporary academic Art History can benefit from the material and technical knowledge of conservators.